2012
DOI: 10.5222/jtaics.2012.064
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gabapentin Premedication on the Emergence Delirium in Pediatric Patients Undergoing Circumcision Under Sevoflurane Anesthesia

Abstract: ÖZETAmaç: Gabapentin anksiyolitik ve analjezik etkileri nedeniyle kullanılan antiepileptik bir ajandır. Gabapentinin perioperatif dönemde kullanımı son yıllarda çalışılmıştır.Biz bu çalışmada gabapentinin sevofluran anestezisi altında sünnet yapılan çocuklarda postoperatif analjezik tüketi-mine ve derlenme ajitasyonu üzerine etkisini incelemeyi amaçladık.Gereç ve Yöntem: Yaşları 3'ten büyük 25 ASA I-II grubu sünnet yapılacak çocuk, bu prospektif randomize çalışmaya dahil edildi. Gabapentin grubuna(grup G,n=12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Another study revealed that gabapentin premedication in children reduced postoperative analgesic consumption and attenuated emergence agitation after sevoflurane anesthesia, which is in accordance with the current study [23]. Moreover, Donmez et al [24] concluded that gabapentin reduced agitation after circumcision using sevoflurane in pediatrics.…”
Section: Discussionsupporting
confidence: 90%
“…Another study revealed that gabapentin premedication in children reduced postoperative analgesic consumption and attenuated emergence agitation after sevoflurane anesthesia, which is in accordance with the current study [23]. Moreover, Donmez et al [24] concluded that gabapentin reduced agitation after circumcision using sevoflurane in pediatrics.…”
Section: Discussionsupporting
confidence: 90%
“…Aslı Donmez et al . [ 19 ] agreed with our results as they concluded that gabapentin reduced EAS at 10 min after circumcision using sevoflurane in pediatrics, but they disagreed with our result regarding pain as they demonstrated that gabapentin had no effect on pain score.…”
Section: Discussionsupporting
confidence: 69%